Activity Rhyming Words for Early Childhood to Develop Language - Sakulparak, Warunee (ASEAN Journal of Education, 2023)
Rhyming words teach children to speak with expressions, emphasizing certain words. The rhythm and variation is what helps children learn. The most important part of learning rhymes is separating syllables and phonemes into words. Grouping words will also help children learn and understand words, letters and sounds more deeply and will better prepare children for reading.